Case Report: Successful Intravenous Lipid Emulsion Therapy for Canine Amphetamine Toxicosis - Harris, Stephanie; McMichael, Maureen A.; Harmon, Roy; Boothe, Dawn (Frontiers in Veterinary Science, 2022)
A four-year old, female-spayed, mixed breed dog, weighing 24.2 kg, was presented for acute ingestion of approximately 12.3 mg/kg of an extended-release amphetamine medication. In dogs, the oral median lethal dose for amphetamine ranges from 9-11 mg/kg for methamphetamine hydrochloride to 20-27 mg/kg of amphetamine sulfate. On presentation, the patient was agitated, tachycardic and hypertensive. Initial treatment was instituted with intravenous lipid emulsion therapy (IVLE), and baseline and post treatment amphetamine concentrations were quantified in serum and plasma. In both serum and plasma, post IVLE concentrations of amphetamine were lower one hour after treatment and IVLE was the only treatment instituted during this time. The dog improved significantly while in hospital and was discharged less than 24 hours after presentation. This is the first known reported use of IVLE for treatment of amphetamine toxicosis with documented decreases in both serum and plasma amphetamine levels shortly after administration of IVLE.